2010
DOI: 10.17796/jcpd.34.3.k15t8q1805538524
|View full text |Cite
|
Sign up to set email alerts
|

Mineral Content Removal after Papacarie Application in Primary Teeth: A Quantitative Analysis

Abstract: The aim of this study was to quantify the mineral content removed from primary teeth after using a chemomechanical system, called Papacarie®. Materials: Twenty human primary extracted molars were divided into two groups of 10 specimens each. Group A presented sound molars and Group B decayed molars on the occlusal or occlusal-proximal surface. In Group A, cavities in enamel and dentin with high speed drills were made before treatment. All teeth were treated with Papacárie® following the manufacturer's instruct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 8 publications
3
21
0
3
Order By: Relevance
“…Many studies have reported that Carisolv gel has no adverse effect on the mineral content of dentine. [35][36][37] Sakoolnamarka et al 38 and Hamama et al 39 reported that the Ca:P ratio of residual dentine following Carisolv removal of carious dentine did not significantly differ from the Ca:P ratio of sound dentine. This may imply that Carisolv is an effective method of removing caries-infected dentine.…”
Section: Carisolv Instrumentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have reported that Carisolv gel has no adverse effect on the mineral content of dentine. [35][36][37] Sakoolnamarka et al 38 and Hamama et al 39 reported that the Ca:P ratio of residual dentine following Carisolv removal of carious dentine did not significantly differ from the Ca:P ratio of sound dentine. This may imply that Carisolv is an effective method of removing caries-infected dentine.…”
Section: Carisolv Instrumentsmentioning
confidence: 99%
“…60 Although the results of this study showed no adverse effects, further animal studies are needed to evaluate the effect of Papacarie on dental pulp tissue. Furthermore, only two studies have evaluated the effect of Papacarie gel on the mineral content of deciduous 37 and permanent 39 residual dentine using atomic absorption spectrophotometry and energy dispersive X-rays respectively. The results of both studies revealed that Papacarie gel has no adverse effect on the mineral content of the residual dentine.…”
Section: Mechanism Of Actionmentioning
confidence: 99%
“…Todos esses métodos têm como objetivo reduzir a necessidade de anestesia local, diminuir a sintomatologia dolorosa e eliminar o desconforto sonoro proveniente do uso das brocas 6,17,18,19,20 . As soluções químicas empregadas na remoção de dentina cariada foram desenvolvidas com base no processo de amolecimento do tecido cariado com sua posterior remoção através de instrumentos manuais, preservando estruturas dentárias, não causando irritação pulpar ou desconforto para o paciente 13,18,20,21,22,23,24,25 . A dentina infectada possui uma consistência amolecida/umedecida e alta concentração de bactérias, não podendo ser reparada devido à desnaturação irreversível das fibras de colágeno.…”
Section: Introductionunclassified
“…The conventional method for caries removal is drilling with dental burs. 1 However, drilling may cause adverse biological reactions to dental pulp tissues and non-selectively remove both infected and sound dental tissues. Importantly, drilling can cause anxiety, fear, and pain in patients and frequently requires a local anesthetic injection.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, drilling can cause anxiety, fear, and pain in patients and frequently requires a local anesthetic injection. 1,2 Fear and anxiety in children are known barriers to acceptance of dental treatment. Compliance by some children in dental care can be poor, even with good behavior management.…”
Section: Introductionmentioning
confidence: 99%